(Spectro)Electrochemistry of 3‐(Pyrid‐2‐yl)‐s‐Tetrazine‐ and 1, 2‐ (Dihydro)pyridazine Tricarbonylrhenium(I)chloride. Issue 10 (17th March 2022) - Schnierle, Marc; Winkler, Mario; Filippou, Vasileios; van Slageren, Joris; Ringenberg, Mark R.
Abstract: The electrochemistry and spectroelectrochemistry (SEC) of the three [ReCl(CO)3 (N N)], N N=3‐(pyrid‐2‐yl)‐1, 2, 4, 5‐tetrazine [1], 3‐(pyrid‐2‐yl)‐4‐ferrocenyl‐4, 5‐dihydropyridazine [1H2 Fc], and 3‐(pyrid‐2‐yl)‐4‐ferrocenyl‐pyridazine [1Fc], are reported. The ligand's conjugation affects the reduction potentials as well as intramolecular charge transfers observed in the UV‐vis‐NIR spectrum. The spectroscopic observations were further supported by DFT calculations. Abstract : Tetrazine ligand modification through [4+2] cycloaddition of ferrocenyl olefins, color arises from dramatic change in the LUMO energy of the ligand.